Stres Pengasuhan Orang Tua dari Anak dengan Diabetes Mellitus Tipe 1 di Era Pandemi COVID-19 - Yersi Ahzani; Nur Agustini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the parenting stress experienced by parents who have children with type 1 diabetes mellitus and the factors that influence it. The method used in this research is literature study using Online Database Science Direct, Clinical Key, Scopus, Google Scholar, and ProQuest. The results showed that there are two main themes identified, namely parenting stress and factors that influence parenting stress in parents with type 1 diabetes mellitus. Parenting stress increases in parents who have children with type 1 diabetes mellitus and mothers have higher stress levels than dad. Factors that influence parenting stress consist of the child's age, the child's HbA1c value and time since diagnosis, the sex of parents based on the role of father and mother, economic status, marital status and parents' employment status. In conclusion, there are various characteristics of the child and the characteristics of parents that can be factors that influence parenting stress. The factor HbA1c score and age of the child were most frequently associated with parenting stress. Keywords: Type 1 Diabetes Mellitus, Parents, COVID-19 Pandemic, Parenting Stress